Immature Platelet Dynamics in Immune-Mediated Thrombocytopenic States - Reeves, Hollie M.; Maitta, Robert W. (Frontiers in Medicine, 2020)
A major challenge encountered by clinicians is differentiating presentations characterized by significant thrombocytopenia due to overlapping clinical symptoms/signs and ambiguous laboratory results. Immature platelets represent the youngest platelets that can be measured in the peripheral blood by current hematology analyzers. These young platelets are larger and newly released from the bone marrow. Thrombocytopenic presentations caused directly or indirectly by immune responses can lead to compensatory bone marrow responses seeking to normalize the platelet count, thus obtaining absolute immature platelet counts may be informative while triaging patients. Over the last decade, their use has expanded beyond being an early biomarker of bone marrow reconstitution post hematopoietic stem cell transplantation to being used to establish bone marrow responses to infection and thrombocytopenias due to immune etiologies. Its accessibility as part of more detailed platelet indices obtained with routine laboratories makes it a promising option to understand the bone marrow’s real-time response to disease states characterized by thrombocytopenia. This review will look at the immature platelet count as a biomarker, while presenting current attempts trying to understand how it could be used in thrombocytopenias occurring secondary to a given immune etiology.